Stressed banks? Evidence from the largest-ever supervisory review - Puriya Abbassi; Rajkamal Iyer; José-Luis Peydró; Paul E. Soto (Deutsche Bundesbank, 2020)
Regulation needs effective supervision; but regulated entities may deviate with unobserved actions. For identification, we analyze banks, exploiting ECB's asset-quality-review (AQR) and supervisory security and credit registers. After AQR announcement, reviewed banks reduce riskier securities and credit (also overall securities and credit supply), with largest impact on riskiest securities (not on riskiest credit), and immediate negative spillovers on asset prices and firm-level credit supply. Exposed (unregulated) nonbanks buy the shed risk. AQR drives the results, not the end-of-year. After AQR compliance, reviewed banks reload riskier securities, but not riskier credit, with medium-term negative firm-level real effects (costs of supervision/safe-assets increase).
Keywords: E58; G21; G28; H63; L51; 330; Asset quality review; stress tests; supervision; risk-masking; costs of safe assets